L’EFFET DE L’ORIENTATION DES FIBRES SUR LE COMPORTEMENT MECANIQUE DES STRUCTURES EN MATERIAUX COMPOSITES STRATIFIES. - CHENINE HALIMA (My University, 2010)
The composite laminates have found widespread applications in various fields of construction such as aerospace, marine, and automotive. The high stress due to the discontinuity or sudden change of geometry is known under the name of stress concentration. To design structures with notches, the precise knowledge of stress and stress concentration factor at the bottom notch is required. The cuts are also areas of birth of microcracks that spread to the collapse of the structure. In this study we consider a parametric evades composite laminate structures. The aim of this research is to study the effect of fiber orientations on the variation of stress concentration factor giving a laminate with a single and multiple layers in the presence of notch. The variation of the stress intensity factor for a crack emanating from notch will be highlighted. The analytical treatment for this type of problem is very difficult and therefore we use numerical modeling using codes ABAQUS and ANSYS. Results show that whatever the empilement the maximum deformation is obtained for the lowest interdistance between crack -notch and the instability at crack tip. In fact efforts are resistant to the phenomena that occur at interfaces, such as delamination or friction between the plies. So the presence of a hole causes a reduction of the ligament surface and subsequently the creation of compressive stresses which show the stresses that may cause tearing initiation of delamination.
Keywords: Stress concentration, Stress intensity factors, Stratified, Delamination, Finite elements analysis.